AN ANALYSIS OF ARISTOTLE'S RHETORIC IN THE KOMPAS TV PROGRAM "GOENAWAN MOHAMAD'S TEARS: DO THE PEOPLE BELIEVE JOKOWI, THE CHIEF JUSTICE OF THE CONSTITUTIONAL COURT, OR GIBRAN?" - Hafidloh, Nurul; Febriana, Poppy (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the persuasive strategies of Goenawan Mohamad in an interview on the ROSI talk show broadcast on KOMPAS TV’s YouTube channel, using Aristotle’s rhetorical theory as the analytical framework. The focus is on how logic (logos), credibility (ethos), and emotion (pathos) are balanced to influence public perception, particularly regarding political stance and democratic discourse. Method: A qualitative research design was employed through in-depth observation and screenshot documentation of the interview, enabling systematic analysis of verbal and non-verbal communication elements such as gestures, facial expressions, and lexical choices. Results: The findings reveal a significant shift in Goenawan Mohamad’s political orientation, transitioning from a strong supporter of Jokowi to a more critical observer. This change is reflected in the rhetorical strategies he employs, which emphasize nuanced credibility and emotional resonance to frame his evolving stance. Novelty: The study contributes to rhetorical and political communication scholarship by contextualizing Aristotle’s classical theory within contemporary Indonesian media, demonstrating how rhetorical analysis can uncover shifts in political alignment and deepen understanding of persuasion in public discourse.